Spiral spin liquid noise - Hiroto Takahashi; Chun-Chih Hsu; Fabian Jerzembeck; Jack Murphy; Jonathan Ward; Jack D. Enright; Jan Knapp; Pascal Puphal; Masahiko Isobe; Yosuke Matsumoto; Hidenori Takagi; J. C. Séamus Davis; et al. (Proceedings of the National Academy of Sciences, 2025)
An emerging concept for identification of different types of spin liquids [C. Broholm et al. , Science 367 , eaay0668 (2020)] is through the use of spontaneous spin noise [S. Chatterjee, J. F. Rodriguez-Nieva, E. Demler, Phys. Rev. B 99 , 104425 (2019)]. Here, we develop spin noise spectroscopy for spin liquid studies by considering Ca 10 Cr 7 O 28 , a material hypothesized to be either a quantum or a spiral spin liquid (SSL). By enhancing techniques introduced for magnetic monopole noise studies [R. Dusad et al. , Nature 571 , 234–239 (2019)], we measure the time and temperature dependence of spontaneous flux Φ ( t , T ) and thus magnetization M ( t , T ) of Ca 10 Cr 7 O 28 samples. The resulting power spectral density of magnetization noise S M ω , T reveals intense spin fluctuations with S M ω , T ∝ ω - α ( T ) and 0.84 < α T < 1.04 . Both the variance σ M 2 T and the correlation function C M t , T of this spin noise undergo crossovers at a temperature T ∗ ≈ 450 mK . While predictions for quantum spin liquids are inconsistent with this phenomenology, those from Monte–Carlo simulations of a two-dimensional (2D) SSL state in Ca 10 Cr 7 O 28 yield overall quantitative correspondence with the measured frequency and temperature dependences of S M ω , T , C M t , T , and σ M 2 T , thus indicating that Ca 10 Cr 7 O 28 is an SSL.